Efficient total synthesis of neocryptolepine and synthetic access to 6-methylquinindoline from a common intermediate - Méndez, María Virginia (2017)
A convenient approach toward the indoloquinolines neocryptolepine and 6-methylquinindoline from a common intermediate, is reported. Both sequences, designed for maximum use of accessible reagents and robust conditions, are straightforward and efficient. They involved the amidation of 2-aminobenzaldehyde (prepared by iron-mediated reduction of 2-nitrobenzaldehyde) with 2-nitrophenylacetic acid, followed by a K2CO3-assisted cyclization to form a 3-(2-nitrophenyl)quinolin-2-one as the common precursor. Me2CO3-mediated N-methylation of the lactam, reduction of the nitro moiety and final cyclization resulted in 55% overall yield of neocryptolepine, whereas cyclocondensation and N-methylation afforded 79% overall yield of 6-methyl quinindoline. Thus, the sequences toward the targets entailed two POCl3-promoted C-N bond forming reactions, two Fe-mediated nitro group reductions and two base-promoted transformations.